What is the role of the bone marrow microenvironment in AML?. Issue 4 (December 2021) - Mulherkar, Nirupama; Scadden, David T.
Abstract: Acute myeloid leukemia (AML) continues to be associated with relapse and resistance to chemotherapy. The bone marrow microenvironment in AML has been shown to regulate responsiveness to chemotherapy and to support disease progression. This review summarizes some recent experimental insights into the crucial role of the bone marrow microenvironment in AML and persistence after chemotherapy.